The Influence of Work Discipline and Work Motivation on Employee Performance in The Medical Rehabilitation Installation of Level II Hospital 03.05.01 Dustira Cimahi City - Samuel, Samuel; Avianti, Widiya; Komar Priatna, Deden (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2024)
The aim of this research is to determine and analyze: (1) Work Discipline (2) Work Motivation; (3) performance; and (4) The influence of work discipline and work motivation on the performance of Level II Hospital Medical Rehabilitation employees 03.05.01. Dustira Cimahi City, both simultaneously and partially. The research method used in this research is a descriptive survey and an explanatory survey, the unit of analysis in this research is the employees of the Medical Rehabilitation Hospital Level II 03.05.01. Dustira Cimahi City with a sample of 30 people. The type of investigation is causality, and the time horizon in this research is cross-sectional. Based on the research results, it was found that Work Discipline for Level II Hospital Medical Rehabilitation employees 03.05.01. Dustira Cimahi City, apparently employees gave good responses, Work Motivation for Level II Hospital Medical Rehabilitation employees 03.05.01. Dustira Cimahi City can generally be said to be good, employee performance at Level II Hospital Medical Rehabilitation employees 03.05.01. Cimahi City's Dustira is currently considered good. Work Discipline and Work Motivation simultaneously influence the performance of Level II Hospital Medical Rehabilitation employees 03.05.01. Dustira Cimahi City. However, work discipline partially influences employee performance more than work motivation. Because work discipline predominantly influences performance, it is the first priority in improving employee performance. then the Level II Hospital Medical Rehabilitation employee 03.05.01. Cimahi City Dustira are advised to consistently maintain existing work discipline, so that they are able to work more professionally.